Migration of the abdominal catheter of a ventriculoperitoneal shunt into the scrotum - Özveren, MF; Kazez, A; Çetin, H; Ziyal, IM (Japan Neurosurgical Soc, 1999)
A 3-day-old male neonate presented with migration of the ventriculoperitoneal (VP) shunt tip through the patent processus vaginalis resulting in scrotal hydrocele. The association of myelomeningocele with hydrocephalus may have been a predisposing factor in this rare complication. Development of scrotal swelling or hydrocele in a child with VP shunt should be recognized as a possible shunt complication.
Keywords: hydrocephalus; myelomeningocele; ventriculoperitoneal shunt; processus vaginalis; scrotum